Do Radiographic and Clinical Parameters in the Setting of a Bunion Predict Second Ray Pathology? - Caitlin K. Gribbin BA; Elizabeth A. Cody MD; Joseph T. Nguyen MPH; Emilie Williamson BS; Scott J. Ellis MD (Foot & Ankle Orthopaedics, 2016)
Category: Bunion Introduction/Purpose: Hallux valgus deformity is well known to cause second ray pathology, commonly manifested as a second hammertoe or second tarsometatarsal (TMT) joint osteoarthritis (OA). This likely results from decreased weight-bearing capacity of the first metatarsal in the setting of worsening metatarsus primus varus, TMT joint hypermobility, or an excessively long second metatarsal or second toe. It is not known for sure, however, which radiographic and clinical factors in the setting of hallux valgus are protective of second ray pathology and which lead to second hammertoe, TMT joint OA, or both. We hypothesized that the formation of second ray pathology would be correlated with increasing age, increased body mass index (BMI), increased hallux valgus angle (HVA), increased intermetatarsal angle (IMA), and increased second metatarsal length. Methods: All consecutive patients who underwent operative reconstruction for symptomatic hallux valgus from January 2007 to July 2015 by the senior author were included. Patients were grouped into those with 1) bunion only 2) bunion with hammertoe and 3) bunion with second TMT joint OA. Preoperative age, sex, and BMI were recorded. Pre-operative HVA, IMA, metatarsus adductus angle (MAA), and first and second metatarsal lengths were measured on weight-bearing anteroposterior (AP) radiographs. Talar-first metatarsal angle was measured on weight-bearing lateral radiographs. One-way analysis of variance (normality demonstrated) and Kruskal-Wallis (normality not demonstrated) were used to assess differences in continuous variables. Post hoc tests were conducted with Bonferroni technique. Associations between discrete variables and the study groups were analyzed using chi-square tests. Results: Increased age was associated with both hammertoe (P = 0.000) and TMT joint OA (P = 0.006). Increased BMI was associated with TMT joint OA (P = 0.016). Increased HVA was associated with both hammertoe (P = 0.039) and TMT joint OA (P = 0.038). When analyzed categorically, 29.7% of patients with TMT joint OA had a moderate HVA (30.0-39.9 degrees) whereas 22.2% of patients with a bunion only had a moderate HVA (P < 0.05). A one-degree increase in HVA was associated with a 5% chance of having a hammertoe as compared to a bunion only. MAA correlated with TMT joint OA (P = 0.048) (Table 1). Conclusion: Our data suggests that increased age (a surrogate for bunion duration) and increased HVA may predispose patients with hallux valgus to second hammertoe and TMT joint OA formation. Increased BMI may lead to the development of TMT joint OA. Increased MAA may predispose to hammertoe formation. Increased MAA may lead to TMT joint OA. Alternatively, increased MAA could result as a consequence of midfoot cartilage and bone loss in the setting of hallux valgus. This data can help surgeons better inform patients about the optimal timing of bunion reconstruction with or without concomitant second ray surgery.